Bank Indonesia's Initiative in Branding Indonesian Islamic Culture through Modest Fashion as a Soft Power Instrument - Afrilia, Tia; Sahide, Ahmad (Padjadjaran Journal of International Relations, 2026)
Modest fashion has evolved into a global phenomenon, representing cultural and religious identity, particularly within Muslim communities. Indonesia, as the country with the largest Muslim population in the world, is leveraging this potential not only in the context of the creative economy but also as a cultural diplomacy through a soft power approach.This research aims to analyze how modest fashion is utilized as an instrument of soft power by Indonesia, focusing on the strategic role of Bank Indonesia in building and promoting a moderate, inclusive, and progressive image of Indonesian Islamic culture on the global stage. Using qualitative research methods that are descriptive and explanatory in nature, data were collected through document analysis, academic literature, and reports on modest fashion programs facilitated by Bank Indonesia. The research findings indicate that Bank Indonesia plays a significant role in integrating economic, cultural, and diplomatic aspects through various initiatives such as the Indonesia Sharia Economic Festival (ISEF) and the Indonesia International Modest Fashion Festival (IN2MF). These initiatives successfully strengthened Indonesia's position as a global hub for modest fashion and built a positive image of Indonesian Islamic culture worldwide. Modest Fashion telah berkembang menjadi fenomena global, mewakili identitas budaya dan agama, terutama di kalangan komunitas Muslim. Indonesia, sebagai negara dengan populasi Muslim terbesar di dunia, memanfaatkan potensi ini tidak hanya dalam konteks ekonomi kreatif tetapi juga sebagai diplomasi budaya melalui pendekatan soft power. Penelitian ini bertujuan untuk menganalisis bagaimana mode modest dimanfaatkan sebagai alat soft power oleh Indonesia, dengan fokus pada peran strategis Bank Indonesia dalam membangun dan mempromosikan citra budaya Islam Indonesia yang moderat, inklusif, dan progresif di panggung global. Metode penelitian kualitatif yang bersifat deskriptif eksplanatif, data dikumpulkan melalui analisis dokumen, literatur akademik, dan laporan program mode modest yang difasilitasi oleh Bank Indonesia. Hasil penelitian menunjukkan bahwa Bank Indonesia memainkan peran signifikan dalam mengintegrasikan aspek ekonomi, budaya, dan diplomatik melalui berbagai inisiatif seperti Indonesia Sharia Economic Festival (ISEF) dan Indonesia International Modest Fashion Festival (IN2MF). Inisiatif-inisiatif ini berhasil memperkuat posisi Indonesia sebagai pusat mode modest global dan membangun citra positif budaya Islam Indonesia secara global.